FORMULASI TEPUNG BEKATUL DAN TEPUNG TEMPE TERHADAP MUTU KIMIA, NILAI ENERGI, DAN MUTU ORGANOLEPTIK SEREAL FLAKES UNTUK OBESITAS PADA ANAK - ericha dianingtyas; Sulistiastutik .; I Komang Suwita (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2018)
The purpose of this study was to determine the effect of bran flour and tempeh flour formulation on chemical quality, energy value, and organoleptic quality of flakes cereals for obesity in children. This research is an experimental laboratory research with a completely randomized design design using 3 stage treatment so that the proportion of bran flour and tempe flour F1 (88: 12), F2 (82: 18), and F3 (76: 24). The results showed that the proportion of significant influence on the quality of ash, fat and carbohydrates. Organoleptic quality (color, aroma, taste and texture) does not have a significant effect.